Reproducibility of pacing strategy during simulated 20-km cycling time trials in well-trained cyclists - Thomas, K.; Stone, M. R.; Thompson, K. G.; St. Clair Gibson, A.; Ansley, L. (European Journal of Applied Physiology, 2012)
The aim of the study was to assess the reproducibility of pacing strategy, physiological and perceptual responses during simulated 20-km cycling time trials. Seventeen well-trained male cyclists ( [(V)\dot]\textO2 maxVO2max = 4.70 ± 0.33 L min-1) completed three 20-km time trials on a Velotron Pro cycle ergometer within a maximum duration of 14 days. During all trials power output, cadence and respiratory exchange were recorded throughout, rating of perceived exertion and affective response were recorded every 2-km and capillary blood was sampled and assayed for the determination of lactate concentration every 4-km. Power output data was assigned to 1-km `bins` and expressed relative to the mean to quantify pacing strategy. Reproducibility of the pacing strategy and the whole trial mean responses was subsequently quantified using typical error (TE) with 90% confidence intervals. The pacing strategy adopted was similar across repeat trials, though there was a higher degree of variability at the start and end of the trial (TE = 6.6 and 6.8% for the first and last 1-km), and a trend for a progressively blunted start on repeat trials. The reproducibility of performance, cardiorespiratory and perceptual measures was good (TE range 1.0-4.0%), but blood lactate exhibited higher variability (TE = 17.7%). The results demonstrate the performance, perceptual and physiological response to self-paced 20-km time trials is reproducible in well-trained cyclists. Future research should acknowledge that variability in pacing strategy at the start and end of a self-paced bout is likely regardless of any intervention employed.